2019
DOI: 10.1007/s00415-019-09598-1
|View full text |Cite
|
Sign up to set email alerts
|

Survival in treated idiopathic normal pressure hydrocephalus

Abstract: Objective To describe survival and causes of death in 979 treated iNPH patients from the Swedish Hydrocephalus Quality Registry (SHQR), and to examine the influence of comorbidities, symptom severity and postoperative outcome. Methods All 979 patients operated for iNPH 2004–2011 and registered in the SHQR were included. A matched control group of 4890 persons from the general population was selected by Statistics Sweden. Data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 27 publications
2
34
2
1
Order By: Relevance
“…There were proportionally more deaths in those presenting Alzheimer’s disease (AD)-related pathology and in those with an increased comorbidity burden. While the comorbidity burden in our study is in line with a recent Swedish study [ 18 ], it is notable that even in Finnish cohorts with similar follow-up periods, AD-related pathology has not always been associated with increased mortality [ 25 ]. This difference might be due to the used model, as the previous study did not take into account the comorbidity burden in their model [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There were proportionally more deaths in those presenting Alzheimer’s disease (AD)-related pathology and in those with an increased comorbidity burden. While the comorbidity burden in our study is in line with a recent Swedish study [ 18 ], it is notable that even in Finnish cohorts with similar follow-up periods, AD-related pathology has not always been associated with increased mortality [ 25 ]. This difference might be due to the used model, as the previous study did not take into account the comorbidity burden in their model [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…The death certificates were obtained from the database of Statistics Finland. Causes of death were classified using ICD-10 diagnosis codes (International Statistical Classification of Diseases and Related Health Problems 10th revision) and were grouped according to a larger iNPH survival study [ 18 ].…”
Section: Brief Summary Of Methods Used In Original Cohort Studymentioning
confidence: 99%
“…Idiopathic normal pressure hydrocephalus (iNPH) is characterized by gait, cognitive and urinary impairments with ventriculomegaly at brain imaging (Gallia, Rigamonti, & Williams, 2006; Relkin, Marmarou, Klinge, Bergsneider, & Black, 2005; Williams & Malm, 2016). Symptoms can be partially reverted by CSF flow diversion with invasive shunt neurosurgery, making iNPH the leading cause of reversible dementia (Andrén et al, 2020; Halperin, Kurlan, Schwalb, & Cusimano, 2015; Todisco et al, 2020; Wallenstein & McKhann, 2010). The prevalence of iNPH is estimated at 6% in adults older than 80 years (Jaraj et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The long-term effect in shunt responders has been described as encouraging with regard to survival and quality of life. 21,55,58,59 Nevertheless, although some studies showed sustained and beneficial improvement of shunting in more than 50% of patients after 5-year follow-up, 23,60 other studies demonstrated loss of benefit in a variable portion of patients. 2 The reasons for these discrepancies are probably related to the syndromic heterogeneity of iNPH.…”
Section: Long-term Outcome Of Shuntingmentioning
confidence: 99%